The Mental Health Association of San Francisco Partner Organizations Meet Their Goals in Stigma Reduction Efforts Results of a Qualitative Evaluation of the Technical Assistance Process - Cerully, Jennifer L. (RAND Corporation, 2015)
This report describes the results of RAND's evaluation of the San Francisco-based Center for Dignity, Recovery, and Empowerment's technical assistance program for stigma-reduction programs through interviews with community-partner participants.